1996
DOI: 10.1080/15513819609168719
|View full text |Cite
|
Sign up to set email alerts
|

Multinodular Hyperplastic Pannephric Nephroblastomatosis with Tubular Differentiation: A New Morphologic Variant

Abstract: We report a case of bilateral nephromegaly detected prenatally with oligohydramnios. Delivered at 35 weeks, this black male infant rapidly developed renal failure, requiring dialysis. He lived 3 1/2 months. The kidneys were three times normal size and diffusely multinodular, with hypoplastic calyces, no corticomedullary demarcation, and no pyramids. Histologically, they revealed hyperplastic embryonal rests composed of tubules and ducts with prominent branching. The nodular rests were intermixed with areas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The case published in 1994 contained a more classical renal blastemal comprising confluent perilobar nephrogenic rests with an associated renal dysplasia. On the other hand, the 1996 case had tubular differentiation resembling the epithelial component of some Wilms tumors [10,11]. Lastly, a more recent report on two siblings with bilateral nephromegaly and autopsy proven universal NB, suggested an autosomal recessive mode of inheritance [12].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The case published in 1994 contained a more classical renal blastemal comprising confluent perilobar nephrogenic rests with an associated renal dysplasia. On the other hand, the 1996 case had tubular differentiation resembling the epithelial component of some Wilms tumors [10,11]. Lastly, a more recent report on two siblings with bilateral nephromegaly and autopsy proven universal NB, suggested an autosomal recessive mode of inheritance [12].…”
Section: Discussionmentioning
confidence: 94%
“…The autopsy revealed generalized visceromegaly, islet cell hyperplasia and hypertrophy, and nephroblastomatosis. Several small series and single case reports of NB detected at autopsy have followed over the course of the next three decades [8][9][10][11]. A series by De Chadarevian et al described four children with nephromegaly detected on physical examination and confirmed by imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Universal (panlobar) type indicates total replacement of the renal lobe by nephrogenic tissue 1 . Massive renal involvement and pulmonary hypoplasia due to compression of enlarged kidneys make this extremely uncommon disease usually incompatible with life 4 .…”
Section: Discussionmentioning
confidence: 99%